2022
DOI: 10.1021/acs.bioconjchem.2c00078
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Head-to-Tail Cyclic Peptide DNA-Encoded Libraries Using Two-Directional Synthesis Strategy

Abstract: Macrocyclic peptides are an important class of therapeutic agents for the biological targets that are difficult to modulate by small-molecule compounds. Meanwhile, DNA-encoded library technology (DELT) provides a powerful platform for hits discovery. The unity of both fields has proven highly productive in finding cyclic peptide hits against diverse pharmaceutical proteins. Many researchers have extended the chemical toolbox for constructing head-to-tail macrocyclic DNA-encoded libraries with various ring size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…HATU in the cosolvent system has been successfully applied for constructing DEL peptides. 25 Our data further confirmed that HATU is an efficient coupling reagent for the acylation of primary amines. However, we were not able to observe acylation to the DNA-conjugated secondary amine ( Table 3 ).…”
Section: Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…HATU in the cosolvent system has been successfully applied for constructing DEL peptides. 25 Our data further confirmed that HATU is an efficient coupling reagent for the acylation of primary amines. However, we were not able to observe acylation to the DNA-conjugated secondary amine ( Table 3 ).…”
Section: Results and Discussionsupporting
confidence: 77%
“…We repeated the coupling between Fmoc-Leu-OH and the four DNA conjugates ( 1–4 ) in mixed solvents containing water and an organic cosolvent (Table ). HATU in the cosolvent system has been successfully applied for constructing DEL peptides . Our data further confirmed that HATU is an efficient coupling reagent for the acylation of primary amines.…”
Section: Results and Discussionsupporting
confidence: 74%
“…In the following years, additional on-DNA cyclization methods were explored, including amide coupling, S-arylation, Ru catalyzed ring closing metathesis, thioether, 2-substituted isoindole, dihydroquinazolinone and benzimidazole formation (Figure ). Despite these efforts, methodologies for on-DNA macrocyclization are still limited in diversity. Some of the reported reactions also suffer from incomplete cyclization and unwanted side reactions that complicate hit validation.…”
mentioning
confidence: 99%